Uma análise dialógica da transgressão do feminino no filme Alice no país das maravilhas - Ribeiro, Caio Gomes (2016)
The main theme of this dissertation is the axiological and feminine standing before a society that is overwhelmingly run by men and their behaving rules for women. In order to show such standing, we have used the movie Alice no País das Maravilhas, directed by Tim Burton in 2010, thus making it the corpus of this work. As our theoretical framework, we will apply some of Mikhail Bakhtin’s linguistic reflections about dialogical relations, responsible act, ideology and chronotope. We will also employ some contributions by other specialists on the bakhtinian thought, such as Amorim (2014), Barros (2005), Brait (2005; 2012) and Marchezan (2014). All of these reflections will be related to sociological and anthropological studies on feminism as an ideological movement in the search for equality of rights between men and women. More specifically, we have approached some considerations by Kollontai (1977), Paglia (1994) and Rago (1998). Therefore, this research is justified because, upon the analysis of the movie Alice no País das Maravilhas in comparison to the literary work, it was possible to observe not only the amount of dialogical relations that should be studied, but also that the discussions around feminism are still so present in today's society. Considering this scenario, our main aim is to show the constitution of hero Alice and in what ways she is able to react to the customs and values attached to the 19th -century woman, demonstrating how the dialogical relations, as proposed by Bakhtin, are part of this constitution, and in this subject's axiological standing when interacting with others. In oder to achieve this aim, we will analyze Alice's path before, during and after her being in Wonderland, reproducing the enunciates that are essential to this dialogical formation. The observations are restricted only to enunciates from the movie that were reproduced in the dissertation in order to show how the hero Alice is constituted in a dialogical way in relation to the subjects she lived together in Wonderland, trying, this way, to reach the main aim previously mentioned. The analyses allowed us to see that Alice showed signs of transgression of the feminine; However her ideals were misunderstood by the society in which she was inserted. Upon her entrance in Wonderland and the establishment of dialogical relations between Alice and the subjects found there, Alice was able to reflect on her social role and understand her ideological values leading her to stand responsively before the costumes attached to women in 19th century. These signs were only possible to be grasped thanks to the dialogical relations which have shown to be inherent to Alice's constitution as a dialogical and a transgressor subject.